Petra - Green, Sara, 1964- (Seven wonders of the modern world (Bellwether Media), 2021)
Presents the history, construction, design, and culture of the ancient desert city of Petra, Jordan, one of the seven wonders of the modern world. Highlights some of the engineering feats of the city, and details the work being done to preserve and protect Petra. Includes color photographs, fact boxes, a timeline, a glossary, and additional resources.